Study of Financial Risk Management in the Multinational Company (Based on Actavis) - Mazadzhiev, Nikolay (Research Papers, 2016)
The purpose of this paper is to cover the gap in the empirical research of the financial risk in the non-financial international corporation. There are many theories and methodologies for assessment of the financial risk of finance entities, but there are not enough such methodologies focusing on the assessment of the risk of the non-financial corporations. The paper is mainly split into two chapters.In the first chapter, the theoretical foundation of the different forms of the financial risk – currency, interest and credit risk is being examined. The currency risk is being split in its turn into three subtypes: translational, transactional and operational. The focus of the proposed research is defined as the transactional currency risk.In the second chapter, an empirical research has been implemented which examines the coverage of the multinational corporation to a transactional currency risk. The author has chosen a methodology which is based on dispersion analysis over a database containing the net income and gross margin denominated in different currencies (27 currencies) monthly figures over several years period. Based on the dispersion analysis, the currencies, which the company has exposure to are classified into four quadrants using 2 criteria: possibility for risk occurrence (according to the standard deviation) and risk impact (according to the currency exposure). Different approaches to risk management are proposed according to the quadrant in which the currency is being situated in. The author has also formulated recommendations for continuation of the research.It is a current topic, having in mind the increasing uncertainty, the companies are operating in, from one side, and the increasing possibilities and instruments of the companies which are managing the risk, from the other side. From that point, the author’s idea to imply a statistical model for managing the currency risk, using data for a real multinational company is turning the paper into an interesting applied scientific research.